Instilling Humanitarian Values from an Early Age: A Phenomenological Study of the Experience of the Second Principle of Pancasila in Elementary Madrasahs - Rajeti Busni; Dila, Resky Rahma (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to examine the practice of humanitarian values in the Second Principle of Pancasila among students of Islamic Elementary Schools (Madrasah Ibtidaiyah), with a focus on the phenomenon of internalization of these values in everyday life. The problem studied is how students interpret and practice humanitarian values in their social interactions. This study uses a phenomenological approach with qualitative methods, involving participatory observation and in-depth interviews with 20 students and 5 teachers at an Islamic Elementary School in Kendari City. The results show that students internalize humanitarian values through acts of solidarity, justice, and mutual assistance in their social lives. Teachers play an important role as facilitators and role models in the formation of these values. The impact of this study shows that the practice of Pancasila values in Islamic elementary schools contributes to the formation of student character based on social and religious values, while strengthening students' national and Islamic identities. The implication of this study is the need to strengthen the character education curriculum based on real social experiences and reflective learning to deepen students' understanding of justice and humanitarian values.